Mapping of the environmental contamination of Toxoplasma gondii by georeferencing isolates from chickens in an endemic area in Southeast Rio de Janeiro State, Brazil - Luciana Casartelli-Alves; Maria Regina Reis Amendoeira; Viviane Cardoso Boechat; Luiz Cláudio Ferreira; João Carlos Araujo Carreira; José Leonardo Nicolau; Eloiza Paula de Freitas Trindade; Julia Novaes de Barros Peixoto; Mônica de Avelar Figueiredo Mafra Magalhães; Raquel de Vasconcellos Carvalhaes de Oliveira; Tânia Maria Pacheco Schubach; Rodrigo Caldas Menezes (Geospatial Health, 2015)
The environmental contamination of Toxoplasma gondii in an endemic area in Brazil was mapped by georeferencing isolates from chickens in farms in the Southeast of the state of Rio de Janeiro. Tissue samples obtained from 153 adult chickens were analyzed by the mouse bioassay for T. gondii infection. These animals were reared free-range on 51 farms in the municipalities of Rio Bonito and Maricá. The ArcGIS kernel density estimator based on the frequency of T. gondii-positive chickens was used to map the environmental contamination with this parasite. A questionnaire was applied to obtain data on the presence and management of cats and the type of water consumed. Of the farms studied, 64.7% were found to be located in areas of low to medium presence of T. gondii, 27.5% in areas with a high or very high contamination level and 7.8% in non-contaminated areas. Additionally, 70.6% kept cats, 66.7% were near water sources and 45.0% were in or near dense vegetation. Humans used untreated water for drinking on 41.2% of the farms, while all animals were given untreated water. The intensity of environmental T. gondii contamination was significantly higher on farms situated at a distance >500 m from water sources (P=0.007) and near (≤500 m) dense vegetation (P=0.003). Taken together, the results indicate a high probability of T. gondii infection of humans and animals living on the farms studied. The kernel density estimator obtained based on the frequency of chickens testing positive for T. gondii in the mouse bioassay was useful to map environmental contamination with this parasite.